A changed reality: Experience of an acceptance and commitment therapy (ACT) group after stroke. Issue 8 (13th September 2020) - Large, Rebecca; Samuel, Victoria; Morris, Reg
ABSTRACT: Copious research on the utility of Acceptance and Commitment Therapy (ACT) in long-term conditions has demonstrated promising results. However, little research has been conducted on ACT within stroke, particularly studies that are qualitative in nature. The aim of this paper was to gain insight into stroke survivors' experiences of ACT and to explore what processes help facilitate adjustment in living with residual disability. Interviews with thirteen stroke survivors following their attendance at a stroke-adapted ACT group were analysed using a grounded theory approach. Stroke survivors varied in age, severity of stroke, limitations and duration since stroke. Interviews revealed a main difficulty of "accepting a changed reality" following stroke. Survivors' narratives regarding their experiences of ACT revealed insight into which processes helped facilitate movement towards accepting symptoms and a changed reality and into helpful and less helpful aspects of the intervention. Stroke survivors find ACT helpful in adjusting to stroke limitations. ACT appears to have potential as a psychological intervention for stroke survivors experiencing psychological distress. Amendments to the format of the intervention to enhance the impact of ACT impact are identified.